Tolerability and safety of weekly primaquine against relapse of Plasmodium vivax in Cambodians with glucose-6-phosphate dehydrogenase deficiency - Sim Kheng (2018)
© 2015 World Health Organization. Background: Primaquine is used to prevent Plasmodium vivax relapse; however, it is not implemented in many malaria-endemic countries, including Cambodia, for fear of precipitating primaquine-induced acute haemolytic anaemia in patients with glucose-6-phosphate dehydrogenase deficiency (G6PDd). Reluctance to use primaquine is reinforced by a lack of quality safety data. This study was conducted to assess the tolerability of a primaquine regimen in Cambodian severely deficient G6PD variants to ascertain whether a weekly primaquine could be given without testing for G6PDd. Methods: From January 2013 to January 2014, Cambodians with acute vivax malaria were treated with dihydroartemisinin/piperaquine on days (D) 0, 1 and 2 with weekly doses of primaquine 0.75 mg/kg for 8 weeks (starting on D0, last dose on D49), and followed until D56. Participants' G6PD status was confirmed by G6PD genotype and measured G6PD activity. The primary outcome was treatment completion without primaquine toxicity defined as any one of: (1) severe anaemia (haemoglobin [Hb] <7 g/dL), (2) a >25 % fractional fall in Hb from D0, (3) the need for a blood transfusion, (4) haemoglobinuria, (5) acute kidney injury (an increase in baseline serum creatinine >50 %) or (6) methaemoglobinaemia >20 %. Results: We enrolled 75 patients with a median age of 24 years (range 5-63); 63 patients (84 %) were male. Eighteen patients were G6PDd (17/18 had the Viangchan variant) and had D0 G6PD activity ranging from 0.1 to 1.5 U/g Hb (median 0.85 U/g Hb). In the 57 patients with normal G6PD (G6PDn), D0 G6PD activity ranged from 6.9 to 18.5 U/g Hb (median 12 U/g Hb). Median D0 Hb concentrations were similar (P = 0.46) between G6PDd (13 g/dL, range 9.6-16) and G6PDn (13.5 g/dL, range 9-16.3) and reached a nadir on D2 in both groups: 10.8 g/dL (8.2-15.3) versus 12.4 g/dL (8.8-15.2) (P = 0.006), respectively. By D7, five G6PDd patients (27.7 %) had a >25 % fall in Hb, compared to 0 G6PDn patients (P = 0.00049). One of these G6PDd patients required a blood transfusion (D0-D5 Hb, 10.0-7.2 g/dL). No patients developed severe anaemia, haemoglobinuria, a methaemoglobin concentration >4.9 %, or acute kidney injury. Conclusions: Vivax-infected G6PDd Cambodian patients demonstrated significant, mostly transient, falls in Hb and one received a blood transfusion. Weekly primaquine in G6PDd patients mandates medical supervision and pre-treatment screening for G6PD status. The feasibility of implementing a package of G6PDd testing and supervised primaquine should be explored. Trial registration: The trial was registered on 3/1/2013 and the registration number is ACTRN12613000003774.